Putting biomechanical information into practical use - Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
In this keynote lecture, activities of the biomechanics research project of The Japan Association of Athletic Federations are first introduced with examples of speed and motion analyses of elite sprinters in world level competitions. The speaker explain various feedback processes of biomechanical information to athletes and coaches, and propose a procedure to bridge the gap between theory and practice. For effective use of biomechanical data in practice, we have to install two kinds of analysis abilities : a qualitative and quantitative analysis abilities. Without one of two abilities we will be unable to be a good sport biomechanist. A sensible quantitative analysis is derived from a sensitive qualitative analysis and the latter is improved by the former.